Outcome of over-sewing reinforcement of gastric staple line during laparoscopic sleeve gastrectomy in morbid obese patients: single center experience - Abdallah, Adel M. (International Surgery Journal, 2018)
Background: During laparoscopic sleeve gastrectomy (LSG), different staple line reinforcement techniques are adopted by many bariatric surgeons, aiming at reducing the incidence of bleeding and leakage from the staple line. Methods: Fifty patients suffering from morbid obesity with body mass index above 35kg/m2 were prepared for LSG. The patients were enrolled in a prospective, randomized controlled study comparing the effect of staple line reinforcement by suture over-sewing versus non-reinforcement. Patients were classified randomly into two groups. In group I, after gastric stapling, the staple line was reinforced by suture over-sewing using continuous extra-serosal invaginating absorbable polyglycol sutures. In group II (non-reinforcement group), staple line over clipping by 10 mm clips was used when needed. Results: Three cases (12%) in group II presented with collected hematomas and staple line bleeding necessitated laparoscopic evacuation and staple line bleeding control by suture over-sewing or additional clipping. In group I, one case (4%) of hematoma responded well to per-cutaneous drainage. There were 2 cases of leakage (8%) in group II versus no detectable cases in group I. Stenosis was detected in one case (4%) in group II while no detected cases in group I. The operative duration was 135 minutes in group II versus 110 minutes in group I. Conclusions: Reinforcement by suture over-sewing of the staple line as a step in LSG is a safe, technically easy, of low cost and can reduce the incidence of postoperative complications as bleeding and leakage although it significantly prolongs the operative time.